Thermal Arrest Memory Effect in Ni-Mn-Ga Alloys - A. Rudajevova (Advances in Materials Science and Engineering)
Dilatation characteristics were measured to investigate the thermal arrest memory effect in Ni53.6Mn27.1Ga19.3 and Ni54.2Mn29.4Ga16.4 alloys. Interruption of the martensite-austenite phase transformation is connected with the reduction of the sample length after thermal cycle. If a total phase transformation took place in the complete thermal cycle following the interruption, then the sample length would return to its original length. Analysis of these results has shown that the thermal arrest memory effect is a consequence of a stress-focusing effect and shape memory effect. The stress-focusing effect occurs when the phase transformation propagates radially in a cylindrical sample from the surface, inward to the center. Evolution and release of the thermoelastic deformations in both alloys during heating and cooling are analyzed.